Graphical user interface for Tourism Decision Support System (TDSS) - Mahamud, Solihah; Masron, Tarmiji; Mohamed, Badaruddin (2013)
Tourism consists of a wide variety of aspects including facilities, activities, services, and industries to deliver a travel experience. This industry depends heavily on information where customers want to acquire enough information about a tourist destination. This paper presents a Web based GIS which designs with user friendly graphic user interfaces (GUI) to help visitors of Langkawi Island choose and plan their activities more effectively to match their personal preferences and constraints. This paper focus on displaying tourism related information in Langkawi Island, which tourist care o restaurants, hotels, and marketplaces and so on, so that customers can easily obtain adequate information and become attracted to visit the island. This paper is part of the Project “Development of Tourism Decision Support System (TDSS)” under Sustainable Tourism Research Cluster (STRC), Universiti Sains Malaysia.